IMPLEMENTASI WISATA HALAL DI NUSA TENGGARA TIMUR: PERSPEKTIF PENDIDIKAN KRISTEN - Adang Nofandi; Rinto Hasiholan Hutapea; Farras Abyan Aziz (Penamas, 2023)
The initiative to create halal tourism in East Nusa Tenggara (NTT) was approved directly by the community and local government because it was considered antithetical to local customs. Indeed, the Vice President of the Republic of Indonesia remarked that the concept of halal tourism is carried out in Indonesia in order to provide halal meals, suitable places of worship, and other halal services. In Indonesia, halal tourism is defined as the provision of friendly halal service facilities for tourists, also known as Muslim-friendly tourism. The rejection of halal tourist development in NTT prompted a study to ascertain the views of local governments, corporate actors, and the general public on halal tourism in East Nusa Tenggara. The findings from this study were examined utilizing social emotion methodologies and Christian religious education. The study's findings found that efforts are being made to maximize the potential of halal tourism in East Nusa Tenggara Province. For starters, social feelings can be leveraged to foster togetherness while enjoying local tourist attractions. Second, Christian education incorporates societal reform based on God's command and the love for God concept in welcoming others. It promotes acceptance of God's creatures and equitable treatment of them.